ACOG and SMFM guidelines for prenatal diagnosis: Is karyotyping really sufficient? - Hay, Sara B. (Prenat Diagn, 2018)
OBJECTIVE: The American College of Obstetricians and Gynecologists (ACOG) and Society for Maternal‐Fetal Medicine (SMFM) recommend chromosomal microarray analysis (CMA) for prenatal diagnosis in cases with 1 or more fetal structural abnormalities. For patients who elect prenatal diagnosis and have a structurally normal fetus, either microarray or karyotype is recommended. This study evaluates the frequency of clinically significant chromosomal abnormalities (CSCA) that would have been missed if all patients offered the choice between CMA and karyotyping chose karyotyping. METHODS: A total of 3223 prenatal samples undergoing CMA were evaluated. Cases were categorized into 2 groups: those that met ACOG guidelines for CMA versus those that met ACOG guidelines for either CMA or karyotype. RESULTS: Of the 3223 cases, 1475 (45.8%) met ACOG recommendations for CMA, and 1748 (54.2%) met recommendations for either CMA or karyotype. In patients who could have elected either CMA or karyotype, 2.5% had CSCA that would have been missed if the patient had elected to pursue karyotype. CONCLUSION: This study suggests that 2.5% of patients will have a CSCA that may be missed if the guidelines continue to suggest that CMA and karyotyping have equivalent diagnostic value for patients without a fetal structural abnormality.